Armenia 1613: la misión carmelita y la búsqueda de la unidad - Navarro García, Miguel (Teresianum, 2025)
Abstract En mayo de 1613, los carmelitas descalzos Redento de la Cruz y Bartolomé María viajaron desde Isfahán a Ereván y Echmiadzin bajo las directrices del Papa Paulo V y el Prepósito General, P. Juan de Jesús María. Su misión era negociar con Melquisedec, coadjutor de los armenios cismáticos, en un esfuerzo de Roma por consolidar su influencia sobre las comunidades cristianas en Persia. Durante su viaje, documentaron las negociaciones y observaron la situación política y religiosa de la región, los usos y la organización de los armenios cismáticos, leyendas y referencias históricas, así como la pobreza y explotación de los armenios católicos bajo jurisdicción dominicana. A su regreso, intercedieron en Tabriz ante el Sah Abbas I por la comunidad cristiana persa. Sus informes, entregados en Roma a principios de 1614, revelaron la decadencia de la provincia dominicana en Armenia, lo que llevó al general dominico Serafino Secchi a enviar una misión encabezada por Paolo Maria Cittadini para revitalizar la región. Además, los carmelitas documentaron las prácticas religiosas de caldeos, jacobitas y nestorianos a solicitud del Vaticano, en un contexto de crecientes relaciones de Roma con comunidades cristianas globales. Abstract In May 1613, Discalced Carmelites Redento de la Cruz and Bartolomé María embarked on a journey from Isfahan to Erevan and Echmiadzin under the directives of Pope Paul V and the General Superior, Fr. Juan de Jesús María. Their mission was to engage in negotiations with Melchisedec, the coadjutor of the schismatic Armenians, as part of Rome’s broader strategy to consolidate its influence over Christian communities in Persia. Throughout their journey, they meticulously documented the negotiations and provided detailed observations on the region’s political and religious dynamics, as well as the customs and organizational structures of the schismatic Armenians. They also reported on the poverty and exploitation faced by the Armenian Catholics under Dominican jurisdiction. Upon their return, they interceded in Tabriz with Shah Abbas I on behalf of the Persian Christian community. Their reports, delivered to Rome in early 1614, highlighted the decline of the Dominican province in Armenia, prompting Dominican General Serafino Secchi to dispatch a mission led by Paolo Maria Cittadini to revitalize the area. Additionally, the Carmelites recorded the religious practices of Chaldeans, Jacobites, and Nestorians at the Vatican’s request, in a period marked by Rome’s expanding relations with global Christian communities.